Experimental behavior of a masonry wall supported on a RC twoway slab (2015)
This paper discusses the experimental results of a prototype slab-wall that is subjected to vertical and horizontal cyclic loading. The key aspects under discussion are: (a) the differences between the capacity resistance of a wall supported on a slab vs. a wall supported on a fixed base, (b) the implications when shear walls are placed directly on transfer concrete slabs, and (c) the effects that these walls cause on the slabs. The most important results presented herein are the change on lateral stiffness and resistance capacity of the load-bearing wall supported on a slab versus the wall supported on a fixed base. Analytical finite element slab-wall models were built using ANSYS. During the experimental test process of horizontal loading, we detected that the stiffness of the slab-wall system decreased by a third compared to the one on the fixed base wall; a result that supported by the numerical models.